?FACTORS INFLUENCING SEED YIELD IN EARLY INTER-SPECIFIC GENERATIONS OF VIGNA (Biological Sciences - PJSIR, 1994)
Correlation and path coefficient analyses were carried out in early generations of inter-specific crosses between greengram (Vigna radiata L. Wilczek) and blackgram (Vignamungo L. Hepper). Plant height, pod length, pods per plant, biological yield per plant and harvest index were positively correlated with seed yield per plant. Path coefficient analy- sis revealed that harvest index, biological yield per plant and pod weight per plant had a direct positive effect on seed yield per plant. Similarly, seed yield per plant and pods per plant had a direct positive influence on harvest index. It is suggested that biological yield per plant, pod weight per plant and harvest index be used as selection indices for the improvement of seed yield in early generations of inter-specific crosses between greengram and blackgram.